Strategic Lines in the Action Plans of the Educational Inspectorate - Barea Romero, Cristóbal (Avances en Supervisión Educativa, 2024)
The Action Plans of the educational Inspection in Spain traditionally start from strategic or priority lines that establish the educational objectives and consequently their actions for a specific time.The Action Plans of the educational Inspection in Spain traditionally start from strategic or priority lines that establish the educational objectives and consequently their actions for a specific time. The aim of this article is to verify the relationship between the needs of the education system, the priority lines of the departments of education and their translation into the General Action Plans of the Educational Inspection. Common characteristics are deduced and the implications on the organization and operation of the educational inspection from the comparison of the strategic lines present in a sample of Action Plans of the Education Inspection in Spain and their relationship with the rest of the elements of these plans. Finally, conclusions are drawn for more coherence between the established goals and the means to achieve them.